2019
DOI: 10.1017/s1743923x19000321
|View full text |Cite
|
Sign up to set email alerts
|

Islam, Parties, and Women's Political Nomination in Indonesia

Abstract: This article responds to earlier research on the role of Islam as a barrier to women's political nominations by assessing and comparing parties’ efforts to meet institutionally required gender quotas in Indonesia. With the provision of 30% candidate gender quotas implemented since the 2004 elections, how have parties responded? Do Islamist and pluralist parties differ systematically in this regard? More specifically, does religious ideology influence how parties go about meeting quotas, recruiting female candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Research by Fattore et al (2010) drew on survey data to find that there was no support for the proposition that Muslims were opposed to women in political office, with no significant difference in the attitudes of Muslim men and non-Muslim men, and only minor differences between Muslim and non-Muslim women (both of whom were more favourable of women in office than men). Our own national survey, conducted by LSI after the 2019 election, found much variation, but indicated that Muslims were more likely than non-Muslims (64 per cent versus 44 per cent) to agree or strongly agree with the statement “In general, men are more capable of being political leaders.” 6 Meanwhile, Prihatini (2019b) found that Islamist political parties in Indonesia were no better or worse than pluralist or secular parties at recruiting and nominating women.…”
Section: Women Islam and Representationmentioning
confidence: 99%
“…Research by Fattore et al (2010) drew on survey data to find that there was no support for the proposition that Muslims were opposed to women in political office, with no significant difference in the attitudes of Muslim men and non-Muslim men, and only minor differences between Muslim and non-Muslim women (both of whom were more favourable of women in office than men). Our own national survey, conducted by LSI after the 2019 election, found much variation, but indicated that Muslims were more likely than non-Muslims (64 per cent versus 44 per cent) to agree or strongly agree with the statement “In general, men are more capable of being political leaders.” 6 Meanwhile, Prihatini (2019b) found that Islamist political parties in Indonesia were no better or worse than pluralist or secular parties at recruiting and nominating women.…”
Section: Women Islam and Representationmentioning
confidence: 99%
“…In this section, we turn to our fieldwork findings to argue that the fact that presidential and legislative elections were held concurrently provided a boost to campaigns by women candidates, helping to offset at least some of the disadvantages they have previously faced. Those disadvantages are both considerable and well known, and include institutional barriers within the parties, problems of patriarchal culture (Amalia, 2017: 207; Parawansa, 2002: 43), motivation of women themselves to become candidates (Ekawati, 2017: 74), and limited financial resources to fund their campaigns or purchase high list positions from their nominating parties (Prihatini, 2019: 15–16).…”
Section: The Impact Of Simultaneous Elections On Women’s Campaignsmentioning
confidence: 99%
“…In Indonesia, the introduction of an open-list voting system placed greater emphasis on a candidate's campaign and his or her ability to raise funds, placing more financial pressure on women candidates who tend to have less access than men to the clientelistic networks that influence candidate selection and candidate position on the party ticket as well as to the resources needed to engage in the common practice of vote buying. 2 Unsurprisingly, an increasing number of successful women candidates appeared to be relatives of male politicians or dynastic elites who were well-known figures with access to campaign funding (Prihatini, 2019a;Puskapol Universitas Indonesia, 2019a).…”
Section: Indonesia's Legal Candidate Quotamentioning
confidence: 99%